2010
DOI: 10.1152/ajpregu.00739.2009
|View full text |Cite
|
Sign up to set email alerts
|

Age-related prolongation of phase I of V̇o2 on-kinetics in healthy humans

Abstract: Data are lacking regarding age-related modifications of phase I (PhI) of pulmonary Vo(2) on-kinetics during moderate-intensity exercise. We studied three groups (aged 20-30, 40-50, and 60-70 years) of 10 normal subjects, who underwent one incremental and four below-gas exchange threshold constant-power cardiopulmonary exercise tests. Data from constant-power tests were time-aligned and averaged, and the PhI-phase II transition (PhI-IItr) determined when a sharp decrease from baseline of respiratory exchange ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…Recently published data by Mezzani et al (28) found that in older adults (with an experimentally determined phase I of 31 s) using a fixed value of 20 s as the starting point for the fitting of phase II yielded a longer V O 2p of 47 s versus a fit from the experimentally estimated phase I with a V O 2p of 34 s. The present data with a fit from 15 s in O agree that the inclusion of phase I data in the fit can lengthen the phase II (by ϳ6 s). Our results differ from those of Mezzani et al (28) as to the magnitude of the effect of inclusion of the phase I data in the phase II fit. The discrepancy between these studies resides in the strategy used for fitting phase II V O 2p .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Recently published data by Mezzani et al (28) found that in older adults (with an experimentally determined phase I of 31 s) using a fixed value of 20 s as the starting point for the fitting of phase II yielded a longer V O 2p of 47 s versus a fit from the experimentally estimated phase I with a V O 2p of 34 s. The present data with a fit from 15 s in O agree that the inclusion of phase I data in the fit can lengthen the phase II (by ϳ6 s). Our results differ from those of Mezzani et al (28) as to the magnitude of the effect of inclusion of the phase I data in the phase II fit. The discrepancy between these studies resides in the strategy used for fitting phase II V O 2p .…”
Section: Discussionmentioning
confidence: 98%
“…The discrepancy between these studies resides in the strategy used for fitting phase II V O 2p . In the paper of Mezzani et al (28), although the exponential fit function included a TD it is clear that it was not allowed to vary freely; that is, the TD was actually constrained to the fixed duration assigned to the phase I V O 2p (20 s) phase II exponential fit through the 20-s phase I point and resulted in a poor fit of the on transient between 20 and 60 s (see Fig. 1 in Mezzani et al for which the estimated phase II is 57 s versus the fit from 38 s in this subject giving a of 32 s).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The conditional expressions (U 1 and U2) limit the fitting of a particular phase to the period at and beyond the time delay associated with that phase. Fitting the cardiodynamic phase allowed us to more accurately establish the onset of the second phase (25), although this phase cannot be always described by an exponential term (18) and so, only its amplitude and duration (TD 2 Ϫ TD1) are presented ( Table 2).…”
Section: Methodsmentioning
confidence: 99%